2014
DOI: 10.3109/02699206.2013.868518
|View full text |Cite
|
Sign up to set email alerts
|

A cross-etiology comparison of the socio-emotional behavioral profiles associated with attention-deficit/hyperactivity disorder and specific language impairment

Abstract: Cross-etiology comparisons provide important information that can help practitioners establish criteria for differential diagnosis and tailor interventions towards the source of children’s difficulties. This study examined the extent to which parent rating scales of socioemotional behavioral difficulties differentiate cases of attention-deficit/hyperactivity disorder (ADHD) from cases of specific language impairment (SLI), and typical development (TD). Parents of 60 children (7–8 years) completed the Child Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
0
14
0
2
Order By: Relevance
“…In the systematic review, children with ADHD had significantly poorer performance than controls on 11 of the 12 overall language measures ( p < .05; r range: .30–.67). One study found no difference using the CELF‐4 Screening Test ( p = .06, r: .30; Redmond & Ash, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the systematic review, children with ADHD had significantly poorer performance than controls on 11 of the 12 overall language measures ( p < .05; r range: .30–.67). One study found no difference using the CELF‐4 Screening Test ( p = .06, r: .30; Redmond & Ash, ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that removing items reflecting language competence from ADHD scales improves the ability of scales to differentiate between cases of ADHD and language impairment [53], though it is currently unclear whether this is improvement is limited to parent ratings (which appear to be less sensitive to child language ability than teacher ratings). Furthermore, these items may highlight important functional impacts of ADHD and age appropriate language skill may serve as a protective factor in the expression of ADHD in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Because these initial investigations (Redmond, 2011; Redmond & Ash, 2014; Redmond et al, 2011) were directed at examining similarities and differences between children with “pure” SLI and children with “pure” combined-type ADHD, data from children who presented with comorbid ADHD+LI profiles during eligibility testing were not included in those reports. The focus of the present study was on the consequences of co-occurring ADHD+LI, so measurements collected on cases of comorbidity uncovered during recruitment were used in the present analysis ( n = 8).…”
Section: Methodsmentioning
confidence: 99%
“…Redmond (2002) reviewed several commonly used pediatric psychiatric rating scales and found that all of them contained items that could potentially overlap with LIs or academic proficiencies (e.g., “speech problems,” “poor schoolwork,” “does not seem to listen to what is being said to him/her”) and suggested caution when using these tools to identify ADHD and other socioemotional and behavioral disorders in children with LIs. Recently, Redmond and Ash (2014) showed that removing language and academic items from clinical rating scales improved their capacity to differentiate cases of ADHD from cases of SLI without compromising their capacity to differentiate ADHD from typically developing status.…”
Section: Categories Of Comorbiditymentioning
confidence: 99%